(untitled) (University of Denver Undergraduate Research Journal, 2023)
This study examined the factors affecting the presence and occupancy of marabou storks at abattoirs and slaughter slabs near Jinja, Uganda. The average number of storks per unit area was compared across different areas within one large abattoir, including an analysis of the presence of free food, human disturbance, and other scavenging birds (pied crow, piapiac, spur-winged lapwing, and cattle egrets). Occupancy across two abattoirs and one slaughter slab was compared and related to the number of animals slaughtered daily at the facility. Direct observations at abattoirs and slaughter slabs were conducted for ten minutes with five minutes between observations. All observations were taken at the same time of day. Brief interviews with officials at each facility provided information about the number of animals slaughtered and the areas that make up the abattoir. Overall, more marabou storks were found at the largest abattoir, where the most animals are slaughtered daily. More storks were seen in areas where abattoir workers throw the birds offcuts. An apparent association between the number of marabou storks and the level of human disturbance exists, with more storks found in areas of higher disturbance. However, this is likely influenced by the presence of free food. The presence of other scavenging birds did not have any effect on the presence of marabou storks under statistical analysis using a chi-square test (χ², df =1, n = 90, α = 0.01).